2020
DOI: 10.1038/s41421-020-00194-6
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of dimorphic sperm impairs male fertility in the silkworm

Abstract: Sperm, which have a vital role in sexual reproduction in the animal kingdom, can display heteromorphism in some species. The regulation of sperm dichotomy remains a longstanding puzzle even though the phenomenon has been widely documented for over a century. Here we use Bombyx mori as a model to study a form of sperm dimorphism (eupyrene and apyrene sperm), which is nearly universal among Lepidoptera. We demonstrate that B. mori Sex-lethal (BmSxl) is crucial for apyrene sperm development, and that B. mori poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 73 publications
5
60
0
Order By: Relevance
“…To further validate this finding, we repeated the experiment using chromosome 7 stripe paints in whole mount late 5 th instar larval testes (Figure S8). As we predicted based on our testes squashes and previous studies ( 54 and eupyrene (with nuclei) sperm (65)(66)(67)(68)(69)(70)(71). In whole-mount testes, we were clearly able to identify eupyrene secondary spermatocyte bundles (Figure 5C-3) and mature eupyrene sperm (Figures S10 and S11).…”
Section: Telomeres Face Poleward At Random In Metaphase I Bivalents In Testessupporting
confidence: 88%
“…To further validate this finding, we repeated the experiment using chromosome 7 stripe paints in whole mount late 5 th instar larval testes (Figure S8). As we predicted based on our testes squashes and previous studies ( 54 and eupyrene (with nuclei) sperm (65)(66)(67)(68)(69)(70)(71). In whole-mount testes, we were clearly able to identify eupyrene secondary spermatocyte bundles (Figure 5C-3) and mature eupyrene sperm (Figures S10 and S11).…”
Section: Telomeres Face Poleward At Random In Metaphase I Bivalents In Testessupporting
confidence: 88%
“…It promotes the separation of eupyrene sperm bundles and plays an important role in the formation or transport of eupyrene sperm [28,29]. Studies in silkworms have shown that the movement of apyrene sperm is a necessary condition for the transfer of eupyrene sperm from the bursa copulatrix to the spermatheca [30]. Combining the functional roles of apyrene sperm, we speculated that there is no significant difference in the number of eupyrene sperm between the two groups after mating, and the decrease in apyrene sperm may affect the transport from the bursa copulatrix to the spermatheca and fertilization process of eupyrene sperm in females and ultimately affect female egg production.…”
Section: Discussionmentioning
confidence: 99%
“…In lepidopteran insects, there are fertile nucleated eupyrene sperm and infertile non-nucleated apyrene sperm [31][32][33][34][35]. Eupyrene sperm fertilize the eggs, whereas apyrene sperm cannot fertilize the eggs because they lose their nuclei during meiosis [36]. In general, apyrene sperm are produced more or transferred to females more than are eupyrene sperm [37][38][39], although spermatogenesis of eupyrene and apyrene sperm is not markedly different in the diamondback moth Plutella xylostella [40].…”
Section: Sperm Polyphenismmentioning
confidence: 99%